THE EFFECTIVENESS OF ANIMATION VIDEO TO INCREASE ADOLESCENTS’ NUTRITIONAL KNOWLEDGE - Ravi Masitah; Eti Poncorini Pamungkasari; Suminah Suminah (Universitas Airlangga, 2020)
Nutritional needs are important for adolescent to accelerate growth. Good nutritional knowledge in adolescent can help them to consume healthy foods and prevent nutritional problems. Nutrition education with animation video is a great eff ort to improve adolescent nutritional knowledge. The use of attractive, eff ective and effi cient media ease adolescent to understand the nutrition material delivered. The objective of this research was to analyzes adolescent nutritional knowledge after given animation video. This research was quasi experimental with a nonequivalent control group design. There were 84 eeadolescents as research subjects chosen with purposive sampling technique. Animation video was given one time every week for one month with the duration of each video for seven minutes. The data was analyzed using Wilcoxon signed-rank. The results of study showed that nutrition education using animation video gave a positive infl uence on nutritional knowledge of adolescent (p=0.000). Animation video can be used as educational media to improve adolescent nutritional knowledge.